Integral de Riemann e algumas aplicações em matemática, física, economia e biologia - MARIANO, Evandro José da Silva (2022)
This work aimed to bring in a clear and simple language the concepts about RIEMANN’S INTEGRAL studied in the initial calculus subjects of the Full Degree course in Mathematics. It brought in a succinct way a historical contextualization in an attempt to value and perhaps facilitate the understanding of the underlying content in the writing of the text. This work sought to present in a more visual way the processes involving Riemann integral and the main theorems and definitions were approached, such as fundamental theorem of calculus, indefinite and defined integrals, integral by parts, substitution rule, inappropriate integrals, among others . Some of the applications of these concepts were presented in other areas, such as in physics in the work carried out by a force, in the economy in the surplus of consumers and producers, and in biology in cardiac capacity. Such applications illustrate the reason for the importance of learning the concept of integral for various sciences.